Invisible teachers for hidden learners? An investigation into the perceptions of the role of the Learning Support Assistant in the Lifelong Learning Sector - Spenceley, Lydia (2012)
The role of the Learning Support Assistant (LSA) is one that has been widely researched within a compulsory school setting and although continuously evolving is one which is relatively well defined in terms of content and purpose. Within the Lifelong Learning Sector and particularly within the field of Further Education this is not the case and the role, which is funded by the Colleges themselves, is one which is defined by each institution to suit its discrete needs and purposes. Within the literature there is research evidence indicating that the role of the LSA is assuming elements of what has traditionally been the role of the teacher and it is the intention of this investigation, which takes the form of a case study, is to examine the role of the LSA and its relationship with that of the teacher within the special needs area of a single College of further education.